Toxicity of "Bacillus thuringiensis" var. "israelensis" in aqueous suspension on the South American common frog "Leptodactylus latrans" (Anura: Leptodactylidae) tadpoles - Lajmanovich, Rafael Carlos (2015)
The effects of commercial formulations of Bacillus thuringiensis var. israelensis (Bti) on non-target organisms are still a matter of debate; in amphibians, the risks of Bti are little known. To evaluate the toxicity of a commercial liquid (aqueous suspension, AS) formulation of Bti (Introban®) on Leptodactylus latrans tadpoles, including median lethal concentration (LC50) and no-and lowest-observed-effect concentrations (NOEC and LOEC, respectively), as well as the possible effects of Bti on oxidative responses, erythrocytes genotoxicity, and histology of the intestines. In the laboratory, tadpoles were exposed to nominal concentrations of 0 (control), 2.5, 5, 10, 20 and 40mg/L of formulated Bti-AS. Glutathione S-transferase (GST) and catalase (CAT) activities, as well as formation of erythrocyte nuclear abnormalities (ENAs), and histological effect were measured in tadpoles displaying survival rates >85%. L. latrans tadpoles were sensitive to exposure to Bti-AS, reaching 100% mortality after 48h of exposure at the highest concentration. Bti-AS induced GST and CAT enzymes and genotoxicity (erythrocyte's nuclear abnormalities), and caused intestine's histopathology. Our results demonstrate that toxicity of Bti-AS is dose-dependent for L. latrans tadpoles and that sublethal exposure alters enzymes of oxidative stress, induces genotoxicity, and causes intestine damage. Further research is needed to evaluate the ecotoxicological risk of the massive use of Bti formulations on amphibian populations that commonly used suburban wastewater or urban waterbodies to reproduce and where this biopesticide is frequently applied.